Walden Two: A non-aversive utopian society? (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
The fiction novel Walden Two (Skinner, 1948/1975) depicts a society in which the social practices are based in the scientific principles of Behavior Analysis. It involves, basically, the use of positive reinforcement, in contrast to the real societies where aversive control is ubiquitous. Would ‘Walden Two’ really be a culturally planned society based strictly on positive reinforcement contingencies? The present essay is a systematic investigation of the presence or absence of aversive control in Walden Two. The novel was examined, identifying excerpts with key words related to aversive control. Three specific situations were identified, described and analyzed. We argue the inappropriate use of Walden Two as a model of non-coercive society and the need of reevaluating the role of aversive control itself in social relationships, planned or not.
Keywords: Walden Two; utopia; aversive control; Skinner